A wonderful... yet complicated world. (Journal of Parents and Teachers, 2025)
The article is based on seven strategies for educating students in tolerance, as an educator must ensure that integration is universal. However, the natural tendency is for children to group together based on similar affinities, which can lead to marginalization.